The Impact of COVID-19 Among HIV Key Population as Informal Workers - Caroline Thomas; Catherine Thomas; Claudius Novchovick Mone Iye (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Background: HIV cases are still increasing in Indonesia. With the spread of COVID-19, HIV key populations are experiencing undesirable outcomes in social, financial, access to health and food resources. The study aimed to assess the impact of COVID-19 among key populations & PLHIV in Indonesia. Method: Yayasan Peduli Hati Bangsa conducted a participatory research in October to December 2020 to capture and assess the impact of Covid-19, combining and adapting the formats of a ‘Citizen’s report card’, a ‘Community assessment’, and a qualitative survey. Results: Out of 15 participants who were PLHIV and key populations, mostly perceived that COVID-19 had impacted them financially, especially for those who work in informal sectors. Food assistance from the Government was provided at least once a month and the nutritional value was perceived as substandard. Having said that, participants did not consider the nutrition as crucial, as long as they had something to eat. Most of the participants observed that mental health issues were related to their physical health and financial adequacy. Additionally, sources of anxiety arose from the uncertainty in financial income. Lastly, the government was perceived as overly prioritizing COVID-19 while neglecting other health services.Conclusion: Participants in this study wished that government would improve the healthcare and assistance programs for the vulnerable ones affected by COVID-19. Equal and well-targeted distribution of assistance, as well as provision of access to jobs, were the ones that need to be majorly improved by the government.